FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PASAR TENAGA KERJA DAN IMPLIKASI KEBIJAKANNYA TERHADAP SEKTOR PERTANIAN DI KABUPATEN BOGOR - SIREGAR, HERMANTO; SUKWIKA, TATAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
There has been a general concern that after the implementation of the regional autonomy policy, the labor market performance tenfing to decline. This paper aims at analysing various factors influencing the labour market, by making use of an econometric model of simultaneous equation system employing a set of pooled or panel data (combination of yearly time series and 30 subdistricts cross section in Bogor Regency). The results showed that estimated parameters accord well with the theory. The estimated model is fairly good to explain the variation of labor market of Bogor Regency, prior to as well as during the ongoing regional autonomy period. Among the results, it is found that, in agricultural and service sectors, employment absorption for educated and uneducated labours is higher during the autonomy than before the autonomy. The opposite happens in the industrial sector. In all sectors, investment plays an important role in determining employment absorption. Together with labour productivity, employment absorption positively affects gross domestic regional product, which in turns influences a number of labour market variables.
Keywords: Labor Market, Bogor Regency, Agricultural Sector, Econometric Model.